Decision Support System to Determine Scholarship Recipients using Analytical Hierarchy Process Method - Yusup Triwibowo (Institute of Computer Science (IOCS), 2021)
Every year, the Faculty of Engineering, State University of Jakarta, holds the registration for BBM and PPA scholarships. Each scholarship has certain criteria to determine prospective scholarship recipients. The number of determining criteria and the large number of applicants raises the problem of how to determine prospective scholarship recipients with a large number of criteria for a very large number of applicants. To assist the determination in determining eligible students to receive scholarships, a decision support system is needed. This study aims to produce a decision support system application for determining scholarship recipients using a web-based Analytical Hierarchy Process method. This research was conducted at the Faculty of Engineering, State University of Jakarta from March 2015 to October 2015. The method used in making this decision support system uses the Prototype development method. This web-based decision support system for determining scholarship recipients is made using the PHP programming language and MySQL database with XAMPP as the local server. Functional testing of the website was tested by 1 expert (Head of Subdivision for Student Affairs, Faculty of Engineering) by inputting 20 sample data for BBM scholarship applicants and 20 sample data for PPA scholarship applicants in 2015 with 15 students quota for BBM scholarship recipients and 14 students quota for PPA scholarship recipients. Based on the results of the functional test on the sample data entered on the website, 15 students received BBM scholarships and 15 students were not accepted as recipients of BBM scholarships and in the PPA scholarship, 14 students were accepted as recipients of PPA scholarships and 16 students were not accepted as recipients of PPA scholarships. Therefore, it can be concluded that the decision support system using the AHP method functions well and can be used in the process of determining scholarship recipients at the Faculty of Engineering, State University of Jakarta